Appointment time: Disability and neoliberal workfare temporalities - Soldatic, Karen (Sage, 2011)
My primary interest in this article is to reveal the complexity of neoliberal temporalities on the lives of disabled people forced to participate in workfare regimes to maintain access to social security measures and programming. Through drawing upon some of the contemporary debates arising within the social study of time, this article explicates what Jessop refers to as the sovereignty of time that has emerged with the global adoption of neoliberal workfare regimes. It is argued that the central role of temporality within the globalizing project of neoliberal workfare and the positioning of disability within these global macro-structural processes requires the sociological imagination to return to both time as a theme and time as a methodology.